Implementasi Psikologi Humanistik Carl Rogers pada Tradisi Lokal Nyadran di Jambe Gemarang Kedunggalar Ngawi - Wiwik Setiyani (Islamica: Jurnal Studi Keislaman, 2017)
The article discusses nyadran celebration in the village of Jambe Gemarang Kedunggalar Ngawi with a humanistic psychology’s Carls Rogers. The community welcomes the enthusiasm for nyadran, because the event has meaning for abangan community in carrying out the ritual. The enthusiasm of the community with the preparation of ritual ritual: gambyong dance complete with sinden (handlebar), tumpeng, cleansing, offerings and drinks. The purpose of nyadran is for the safety and well-being of the village community of Jambe Gemarang. The humanistic psychology of Carls Rogers contributes to analyzing the implementation of nyadran in building relationships or communications among citizens. The community’s belief in rituals is significant, in particular the belief in sendang as a source of springs and large trees. The behavior of the people who believe in the ritual nyadran image of people who love local traditions and have a personality organism against the positive potentials of the community Jambe Gemarang. The nyadran ritual gives birth to a mature personality and a form of self-actualization of a prosperous society and has the pride of the nyadran tradition as (selfregard) formed from its experiences.